THE RULES OF TURN TAKING STRATEGIES IN ELLEN TALK SHOW - Nur Shabrina Hasan; Sumarsih . . (Universitas Negeri Medan, 2021)
ABSTRACTThe purpose of this research is to analyze the rules realized of turn taking strategies in the Ellen talk show which every conversation always occurs the turn taking to make conversation flows well. In this case the aim of this research is to convey the rules realized of turn taking strategies use by them. The Method of this research use qualitative method. The research question will be answered in analytical description. The collected turn taking strategies is picked up randomly then classified based on the same type. The turn taking strategies is analyzed by using Miles and Huberman and Saldana to see the turn taking which mostly occurs in conversation. The result of this research shows that there are hundred eighty seven data collected from random sampling, those collected data resulted three rules of turn taking strategies: 1.If the current speaker has selected, a particular next speaker, then that speaker should take a turn at the place. 2.If no such selection has been made, then any next speaker may (but need not) self-selection occur, then first speaker has the right to the turn. 3. If no speaker has been selected, unless another speaker may, but need not, continue talking with another turn constructional unit, unless another speaker has self-selected in which case that speaker gains to the right to the turn found in that conversationKeywords: Conversation Analysis, Turn Taking Strategies, Miles Huberman and Saldana, Talk Show.